Selection and characterization of Argentine isolates of Trichoderma harzianum for effective biocontrol of Septoria leaf blotch of wheat - Stocco, Marina Celeste (2016)
Species of the genus Trichoderma are economically important as biocontrol agents, serving as a potential alternative to chemical control. The applicability of Trichoderma isolates to different ecozones will depend on the behavior of the strains selected from each zone. The present study was undertaken to isolate biocontrol populations of Trichoderma spp. from the Argentine wheat regions and to select and characterize the best strains of Trichoderma harzianum by means of molecular techniques. A total of 84 out of the 240 strains of Trichoderma were able to reduce the disease severity of the leaf blotch of wheat. Thirty-seven strains were selected for the reduction equal to or greater than 50 % of the severity, compared with the control. The percentage values of reduction of the pycnidial coverage ranged between 45 and 80 %. The same last strains were confirmed as T. harzianum by polymerase chain reaction amplification of internal transcribed spacers, followed by sequencing. Inter-simple sequence repeat was used to examine the genetic variability among isolates. This resulted in a total of 132 bands. Further numerical analysis revealed 19 haplotypes, grouped in three clusters (I, II, III). Shared strains, with different geographical origins and isolated in different years, were observed within each cluster. The origin of the isolates and the genetic group were partially related. All isolates from Parana were in cluster I, all isolates from Loberia were in cluster II, and all isolates from Pergamino and Santa Fe were in cluster III. Our results suggest that the 37 native strains of T. harzianum are important in biocontrol programs and could be advantageous for the preparation of biopesticides adapted to the agroecological conditions of wheat culture.